Psychological insulin resistance needs psychosocial sensitization - Sanjay Kalra; Amandeep Singh (Journal of the Pakistan Medical Association, 2026)
Insulin Related Emotions For over a century now, insulin has served humankind selflessly. Countless lives have been saved, and strengthened, by the effective management of diabetes. In spite of clear cut evidence regarding the benefits of insulin, however, many people consider it an unwelcome intrusion. This psychological dislike for insulin seems to be deep rooted in many cultures. So much so, that it has been given a formal name: psychological insulin resistance.1 Insulin hesitancy and insulin inertia are commonly faced constraints in our clinical practice.2 Insulin distress, i.e., an emotional response to a suggestion to use insulin; characterized by extreme apprehension, discomfort, dejection, or denial; due to a perceived inability to cope with the requirements of insulin therapy, too, is well known.3 It is important to understand the context in which these phenomena occur. This helps craft suitable therapeutic educational initiatives and interventions, to facilitate the early adoption and acceptance of insulin therapy. Continue...